Model of Tawhid Education in Children: An Ethnographic Study of the Tablighi Jamaah Family in Indonesia - Kaputra, Soni; Rivauzi, Ahmad; Jaafar, Azhar; Kakoh, Nur Asikin (Khalifa Journal of Islamic Education, 2022)
This study aims to explore the educational model of tawhid for children in the Tablighi Jamaah family. The study used a qualitative method with an ethnographic approach. Research data is taken through direct interviews with ten informants (heads of the JamaÃ¡h Tabligh family), to strengthen the interview data the authors conducted observations for two years by being directly involved in the activities of the Tablighi Jamaah such as Ijtima', Bayan Markas, Ta'lim Halaqah, Khuruj, Jaulah, and the author keeps in touch directly to all informants' homes. All interview and observation data were then analyzed thematically using NVivo 12 software. Overall, the results of the analysis showed that there were fifteen educational model of tawhid for children in the Tablighi Jamaat family. The fifteen models are: i) organizing routine ta'lim, ii) creating a religious atmosphere at home, iii) starting activities with tawhid sentence, iv) providing early-agetawhid education, v) involving children on da'wah activities, vi) educating with muzakarah, vii) teaching Islamic etiquette, viii) teaching prayers, ix) persuading children to pray in the mosque, x) be an example in practicing religion, xi) Islamic story-telling xii) practising Monday and Thursdayfasting, xiii) ecnouraging children to khidmat, xiv) playing Islamic songs, xv) monitoring children's worship. The results of this study can be used as initial data for future researchers in examining different issues related to this problem as well as various other issues relevant to this context.